A State of Relief: Feelings, Affect and Emotions in Instantiating the Malawi State in Disaster Relief. Issue 2 (1st September 2022) - Hendriks, Tanja D.
Abstract: Studies of bureaucrats and bureaucracy have contributed to our understanding of the social production of indifference (Herzfeld 1992 ). However, in this article, I argue that this focus obscures the centrality of feelings, affect and emotions in their everyday functioning. Drawing on twelve months of ethnographic fieldwork in Malawi with civil servants of the Department of Disaster Management Affairs, I show empirically how they did not—nor did they strive to—appear indifferent. Rather, feelings, affect and emotions shaped the ways in which they allocated assistance and instantiated the state in the aftermath of Cyclone Idai. Despite its general material constraints, these relief interventions enabled the Malawi state to be present and provide resources to some of its citizens, constituting (it as) a state of relief.